Time & Motion Study II and 'Electric Chair Music' - Ferneyhough, Brian 1943-; Heyde, Neil; Archbold, Paul 1964-; Still, Colin; Lefeber, David; Collins, Sam (London Optic nerve, 2007)
Time & Motion II, Brian Ferneyhough’s extraordinary composition for cello & electronics, was shot in 2005 at a recording session for Métier Records. The cellist is Neil Heyde & electronics are by Paul Archbold. 'Electric Chair Music' is a short documentary in which Ferneyhough & the performers discuss their approaches to this very challenging work.